Physical activity behaviour in middle-aged and older women and men: an analysis of the CLSA - Cassandra D’Amore; Lauren E. Griffith; Julie Richardson; Marla K. Beauchamp (BMC Public Health)
Abstract Background Increasing physical activity (PA) levels can decrease the burden of non-communicable diseases and improve functional ability in aging populations. Understanding current patterns in PA behaviours is essential for developing effective interventions. This study aimed to describe the usual PA by type of activity and amount in middle-aged and older adults. Methods A descriptive cross-sectional analysis of baseline data from the Physical Activity Scale for the Elderly in the Canadian Longitudinal Study on Aging was completed. Subgroup analyses were used to explore PA behaviour, by age and sex, socioeconomic variables, region and season. In addition, we estimated quintiles based on the amount of total PA completed in Canadians 45–85 years. Means and frequencies were reported using inflation weights. Results The 47,840 participants represented our target population of 12,365,513 Canadians 45–85 years old. The mean PASE score was 151 (SD 79.11) with 65% of persons 45–85 years completing at least 150-minutes of moderate-vigorous PA a week. Amount of PA and the proportion of individuals meeting the recommendation decreased for females, and with increasing age, lower income, and less education. Additionally, those with the lowest PA levels were more likely to report limitations in mobility and activities of daily living and had a higher prevalence of some chronic conditions (diabetes, musculoskeletal, and vision). Conclusion Physical activity behaviour among middle-aged and older adults varies based on several characteristics. Targeted interventions and promotion efforts are warranted, particularly for older females and those with lower income and education. Further investigation to determine directionality is needed.